Pengaruh Debt to Equity Ratio, Net Profit Margin, Price to Earning Ratio dan Current Ratio terhadap Return Saham - Muhammad Goerdy; Wida Purwidianti; Restu Frida Utami; Alfalisyado (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The capital market, which is a vital instrument in the modern economy, serves as a meeting place for the supply and demand of investments. Among the various sectors in the capital market, the property and real estate sectors play a significant role, especially in the economy of a country. The purpose of this study is to determine the influence of Debt to Equity Ratio, Net Profit Margin, Price to Earnings Ratio, and Current Ratio on Stock Returns. This research employs a quantitative method and secondary data. The population consists of 89 Property & Real Estate companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023, with a sample size of 91 company data points obtained using purposive sampling technique with unbalanced panel data. Based on data analysis using SPSS Statistics 25, the results indicate that Net Profit Margin has a positive and significant effect on Stock Returns, while Debt to Equity Ratio, Price to Earnings Ratio, and Current Ratio do not have an effect on Stock Returns.